Terapi Murottal terhadap Penurunan Kecemasan Pasien Pre Sectio Caesarea - Alya Islamiaty; Suhermi, Suhermi; Al Ihksan Agus (Window of Nursing Journal, 2023)
Anxiety in pregnant women will increase as the time of delivery approaches, especially when it is known that the pregnancy requires surgery. The treatment of anxiety can be done with non-pharmacological therapy, one of which is murottal Qur'an therapy. This study aims to determine the effect of murottal Qur'an on reducing anxiety levels in preoperative sectio caesarea patients at RSIA Sitti Khadijah Muhammadiyah 1 Makassar. This type of research uses a quantitative research design pre-experimental two groups pre-test-post test. As for the determination of the sample calculated using the Slovin formula, the results obtained were 60 respondents who were divided into two groups, 30 respondents for the intervention group and 30 respondents for the control group using the HARS Scale instrument. The relationship test was carried out using the Paired Sample T Test with an error value of = 0.05. The results of this study indicate that before being given murottal Qur'an therapy the level of anxiety in pregnant women for the intervention and control groups was in the mild to severe anxiety, after being given murottal Qur'an therapy the level of anxiety in pregnant women for the intervention group was at no. there was anxiety to mild anxiety, and the control group remained in mild to moderate anxiety. The conclusion of this study is that there is an effect of murottal Qur'an on reducing anxiety levels in preoperative sectio caesarea patients in the treatment room of RSIA Sitti Khadijah Muhammadiyah 1 Makassar with a value of 0.000 or <0.05. Therefore, the use of murottal Qur'an therapy can be used as a non-pharmacological therapy that can be done independently to reduce anxiety levels.